El devenir de las imágenes en los años de la última dictadura militar argentina: circulación y recepción de las ficciones hermético-metafóricas - Lusnich, Ana Laura (2019)
In the course of the last Argentine military dictatorship (1976-1983), the cinema and the audiovisual media in general became significant actors in the transmission and approval of the policies of the military regime. On the other hand, a no less broad sector maintained a critical and reflective position on the actions of the dictatorship. The objective of this work is to investigate the public evolution of a segment of the film production made in that period -the hermetic-metaphorical fictions that obliquely interpellated the political and social reality of the moment-, with the interest of knowing the degree of acceptance on the part of the public institutions of the time, the spectators and the journalistic media. The work is focused on four films in particular made by two dissident directors of the regime, who were successful in commercial cinemas and generated dissimilar responses in the field of public opinion and the media: The Island (Alejandro Doria, 1979), The Fears (Alejandro Doria, 1980), Time of Revenge (Adolfo Aristarain, 1981) and Last Days of the Victim (Adolfo Aristarain, 1982).